Analisis Faktor-Faktor Yang Mempengaruhi Harga Saham Studi Kasus Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Periode 2012-2014 - Nur Arifa, Fauriza; , Dra. Wafiatun Mukharammah, M.M (2016)
This study aims to identify and analyze the influence of Debt to Equity Ratio, Total Assets Turnover, Devidend Payout Ratio, and Sales Growthon stock prices of companies registered in the period 2012-2014 either multiple regresision analysis or t test result. Data used is secondary data. By using purposive sampling method obtained a total sampel of 16 companies from 17 companies. This study uses multiple linear regression analysis to see the effect of independent variables on the dependent variables.data. The result showed that the simultaneous, Debt to Equity Ratio, Total Assets Turnover, Devidend Payout Ratio, and Sales Growth effect on the stock prices of companies registered in the period 2012-2014. But partially, just Debt to Equity Ratio and Sales Growth that effect stock price. While Total Assets Turnover and Devidend Payout Ratio no effect on stock price. Keywords : Debt to Equity Ratio, Total Assets Turnover, Deviden Payout Ratio, Sales Growth, and the Stock price.